show that the general solution of y' + {[ (y^2)+y + 1]/[x^2+x+1] = 0

is given by x+y+1=A[1-x-y-2xy]

first separate the variables , then, complete the squares in each term, integrate term by term

then use the formula for arctanx+arctany

homogeneous differential equation

prove that [ x^2 - y^2 ]=c [ x^2 - y^2 ]^2 is a solution of

[ x^3 - 3x (y^2) ] dx = [ y^3 - 3x^2y ] dy

solution of homogeneous differential equation from miscellaneous problems of ncert cbse 12th mathematics

solution of a second order differential equation using reduction of order

solve y"-y = 0 if y = coshx is one of the solutions

using the formula for reduction of order

solution of solution of a second order differential equation using reduction of order

### variation of parameter method

solve xy" - 4y' = x^4 by method of variation of parametersolution to problem on differential questions using variation of parameter method

### orthogonal trajectory of y(1+x ² ) = Cx

find the orthogonal trajectory of y(1+x ² ) = Cxanswer to problem on orthogonal trajectory of y(1+x ² ) = Cx

### orthogonal trajectory of y = (k/x)

find the orthogonal trajectory of y = (k/x)solution to find the orthogonal trajectory of y = (k/x)

formulae on integration

PAGE 1 BASIC INTEGRATION

PAGE 2 INTEGRATION BY SUBSTITUTION

PAGE 3 INTEGRATION BY COMPLETION OF SQUARES

PAGE 4 INTEGRATION BY PARTS

PAGE 5 INTEGRATION BY MANIPULATION OF NUMERATOR IN TERMS OF DENOMINATOR

PAGE 6 INTEGRATION USING PARTIAL FRACTIONS

disclaimer:

There is no guarantee about the data/information on this site. You use the data/information at your own risk. You use the advertisements displayed on this page at your own risk.We are not responsible for the content of external internet sites. Some of the links may not work

## No comments:

## Post a Comment

please leave your comments